Prevalence of Probable Sarcopenia and Associated Lifestyle Factors among Elderly Retired Nigerian Soldiers - Ajuonuma FO; Ibrahim BY; Zubairu HD; Butawa NN (Ibom Medical Journal, 2025)
Background: Probable Sarcopenia is the age-related decline in muscle strength. It is a pre-sarcopenic state that is amenable to lifestyle modification. This study aimed to determine the prevalence of probable sarcopenia and the modifiable lifestyle factors associated with it among the elderly retired Nigerian soldiers.